Management and Supervision of Zakat at the National Amil Zakat Agency (BAZNAS) of Bengkulu Province in 2019-2020 - Mardhatillah Suaka; Mardenis Mardenis; Zefrizal Nurdin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This study aims to determine the zakat collection, distribution of zakat, and supervision of BAZNAS Bengkulu Province. The research method used is a juridical empirical type by interviewing directly to the BAZNAS Bengkulu Province and the Bengkulu Provincial Government; after the data has been collected through the interview process, the data is qualitatively processed to explain and expand objective management and oversight of zakat without using the statistical formula. The results of this study (1) The collection of zakat assets is carried out in 3 stages. The planning stage is not carried out with a particular strategy. It is not fixed on a specific schedule, the coordinating stage is carried out directly and indirectly, and the implementation stage is sourced from individual zakat and business entity zakat. (2) Distribution of zakat assets is carried out in 3 stages, namely the planning stage, by forming six work programs. The coordinating stage is carried out by holding a Regional Coordination Meeting (Rakorda). The implementation stage is divided into two: distribution in the form of consumptive zakat distribution and utilization in the form of distribution zakat is productive. (3) Supervision of the BAZNAS Bengkulu Province is carried out internally by the leadership to its staff. External supervision is carried out by the Ministry of Religion, Public Accountants, and the community.